In Vitro and In Vivo Antimalarial Activity Assays of Seeds from Balanites aegyptiaca: Compounds of the Extract Show Growth Inhibition and Activity against Plasmodial Aminopeptidase. (25th May 2011) - Kusch, Peter; Deininger, Susanne; Specht, Sabine; Maniako, Rudeka; Haubrich, Stefanie; Pommerening, Tanja; Lin, Paul Kong Thoo; Hoerauf, Achim; Kaiser, Annette
Abstract : Balanites aegyptiaca ( Balanitaceae ) is a widely grown desert plant with multiuse potential. In the present paper, a crude extract from B. aegyptiaca seeds equivalent to a ratio of 1 : 2000 seeds to the extract was screened for antiplasmodial activity. The determined IC50 value for the chloroquine-susceptible Plasmodium falciparum NF54 strain was 68.26 μ g / μ L ± 3.5 . Analysis of the extract by gas chromatography-mass spectrometry detected 6-phenyl-2(H)-1, 2, 4-triazin-5-one oxime, an inhibitor of the parasitic M18 Aspartyl Aminopeptidase as one of the compounds which is responsible for the in vitro antiplasmodial activity. The crude plant extract had a K i of 2.35 μ g / μ L and showed a dose-dependent response. After depletion of the compound, a significantly lower inhibition was determined with a K i of 4.8 μ g / μ L . Moreover, two phenolic compounds, that is, 2, 6-di- tert -butyl-phenol and 2, 4-di- tert -butyl-phenol, with determined IC50 values of 50.29 μ M ± 3 and 47.82 μ M ± 2.5, respectively, were detected. These compounds may contribute to the in vitro antimalarial activity due to their antioxidative properties. In an in vivo experiment, treatment of BALB/c mice with the aqueous Balanite extract did not lead to eradication of the parasites, although a reduced parasitemia at day 12 p.i. was observed.